Terrestrial alteration mineral assemblages in the NWA 10416 olivine phyric shergottite. (1st July 2020) - Piercy, J.D.; Bridges, J.C.; Hicks, L.J.; MacArthur, J.L.; Greenwood, R.C.; Franchi, I.A.
Abstract: We report on the alteration history of the olivine-phyric, highly depleted (HD) shergottite, Northwest Africa (NWA) 10416, paying particular attention to the origin of the aqueous alteration seen affecting the meteorite's olivine megacrysts. The rock's interior displays 1 mm, zoned, altered olivine megacrysts set in a groundmass of clinopyroxene, unzoned olivine, and interstitial plagioclase and maskelynite. Synchrotron micro X-ray diffraction (µ-XRD) and transmission electron microscopy (TEM) show that plagioclase and maskelynite have been partially replaced by kaolinite. The relict olivine megacryst cores display a unique concentric colouration for martian meteorites, having central amber-coloured zones surrounded by a brown mantle zone, with the rims remaining clear and unaltered. This colouration is a result of fluid alteration and partial replacement, with hydration. TEM analysis revealed the ∼200 nm scale banded and largely amorphous nature of the alteration, but with some (∼20%) relict crystalline olivine patches. Although the coloured olivine zones show cation and anion site vacancies compared to stoichiometric olivine, a relict igneous compositional trend is preserved in the megacrysts, from Mg-rich altered cores (Mg# = 76) to unaltered stoichiometric rims (Fo53 ). Synchrotron Fe-K X-ray absorption near-edge structure (XANES) analysis revealed that the coloured zones of the megacryst have different Fe oxidation values. High ferric contents are present in the brown mantle zones (Fe 3+ /ΣFe ≤ 0.92) and the amber zones (Fe 3+ /ΣFe ≤ 0.30), whereas the clear rims are ferrous. This suggests alteration occurred in an oxidising environment and that the sharp contrast in colour of the megacryst (brown to clear) is a record of a relict fluid reaction front. In order to test the terrestrial or extraterrestrial origin of the alteration, olivine material from a shock-melt vein was analysed by TEM. The analysis revealed 0.952 nm curved d -spacing's from clay alteration undisturbed by any shock effects, strongly suggesting a terrestrial origin. The d-spacing values most likely represent a collapsed saponite or vermiculite, showing that in some places olivine has been replaced by crystalline clay. Oxygen isotope analysis of bulk (Δ 17 O = 0.309 ± 0.009 (2σ) ‰) and amber-coloured megacryst material (=0.271 ± 0.002 (2σ) ‰), are also consistent with terrestrial alteration. We propose a model in which, during the meteorite's time in Northwest Africa, low-temperature, likely acidic, groundwater exploited fractures. The fluid altered the olivine megacrysts in a way that was controlled by the pre-existing, igneous compositional zonation, with Mg-rich olivine being more susceptible to alteration in this fluid environment. The plagioclase and maskelynite were also altered to a high degree. After the alteration event it is likely that NWA 10416 had a significant residence time in Northwest Africa, accounting for terrestrial calcite and the dehydration of some clay phases.